The Effect Of The Healthy Clean Live Knowledge (Phbs) Toward Student Personal Cleanliness By Using A Saintific Approach At The Fourth And Fifth Grade Students In The Environment Of Sd Negeri 04 Minas - Rahmayulis Rahmayulis (Jurnal Ilmiah Pendidikan Scholastic, 2018)
Factors affecting individual health and public health are heredity, environment, behavior and public service (Soekidjo Notoatmodjo, 2010). In addition to factors affecting health, there are factors that influence clean life behavior, among others social class and economy class, knowledge, attitude, health status and personal habits. In relation to this matter, SD Negeri 04 Minas is a Primary School which has applied about healthy clean living in school by giving the material about school environment health. But in reality SD Negeri 04 Minas are less clean and tidy in dressing and shodding, picket cleaning classrooms that should always be reminded, there is a garbage disposal is not in place, students do not wash hands after exercise and before eating, students have cavities, Students have long and unsanitary nails, and students have less clean hair (there are ticks). Based on the phenomenon exists can be concluded that on the students. Based on the background and identification of problems that have been mentioned above, then the problem in this research is "How High Level of Knowledge of Clean Healthy Behavior (PHBS) to Personal Hygiene Student by using scientific approach in Class IV and V at SD Negeri 04 Minas? " The research used in this research is quantitative descriptive research.According Sugiyono (2013: 30-31), quantitative descriptive is research conducted with the main purpose of making an objective description or description of a situation that is about PHBS knowledge of personal hygiene of students by using scientific approach in class IV and V SD Negeri 04 Minas.The method used in this research is with technique of taking data using test.The test is a questionnaire filled by students of grade IV and V of SD Negeri 04 Minas who acts as research respondents.From these results it can be known level of knowledge about PHBS on personal hygiene of students by using scientific approach in class IV and V SD Negeri 04 Minas.The type of data in this study is data taken directly in the field.The study took place from March 2016. Based on the results of research and discussion of researchers in students of Class IV and V SD Negeri 04 Minas presented, it can be concluded that the students of grade IV and V in SD Negeri 04 Minas as much as 66.7% or 28 students into either category, 31.0% or 13 Students enter enough category and 2.4% enter the category less or 1 student.Thus the need for in-depth knowledge and practice repeatedly so that students of grade IV and V SD Negeri 04 Minas on Clean Healthy Behavior (PHBS) on personal hygiene can run continuously.